1979
DOI: 10.1016/0031-9384(79)90407-4
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and vomeronasal system participation in male hamsters' attraction to female vaginal secretions

Abstract: POWERS, J. B., R. B. FIELDS AND S. S. WINANS. O~wtory and vomeronasal system participation in male hamsters' attraction to ./bmc:/e vaginal secrethms. PHYSIOL. BEHAV. 22(I) 77--84, 1979.~The effects of olfactory (OLF) vomeronasal (VN), or combined deafferentations of male hamsters on their attraction to female hamster vaginal secretions (FHVS) were determined using 2 different attraction tests. In the first, FHVS was placed on one wall of a plastic test chamber, while in the second test, FHVS was rubbed onto 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, reproductive experiences have been suggested as playing a role in altering the endocrine status and conferring beneficial changes to females in terms of improving cognition and enhancing some aspects of memory in sexual behavior [ 10 , 11 ]. For example, lesioning the vomeronasal organ (VNO), which is mainly responsible for the perception of sex pheromones, induced a loss of sexual responses in sexually naive males; however, sexual experiences restored such impairment by activating the main olfactory system [ 13 , 47 , 48 , 49 ]. In the current study, reproductive experiences mitigated the disruptive effect of Tph2 knockout and may, thereby, have guided Tph2 −/− female mice toward male urine odor.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reproductive experiences have been suggested as playing a role in altering the endocrine status and conferring beneficial changes to females in terms of improving cognition and enhancing some aspects of memory in sexual behavior [ 10 , 11 ]. For example, lesioning the vomeronasal organ (VNO), which is mainly responsible for the perception of sex pheromones, induced a loss of sexual responses in sexually naive males; however, sexual experiences restored such impairment by activating the main olfactory system [ 13 , 47 , 48 , 49 ]. In the current study, reproductive experiences mitigated the disruptive effect of Tph2 knockout and may, thereby, have guided Tph2 −/− female mice toward male urine odor.…”
Section: Discussionmentioning
confidence: 99%
“…If only volatile chemosignals are available, removal of access to MOE, but not to the VNO, impairs opposite-sex odor attraction in male Syrian hamsters (O’Connell and Meredith, 1984; Powers and Winans, 1973), mice (Pankevich et al, 2004) rats (Dhungel et al, 2011a) and ferrets (Kelliher and Baum, 2001). If direct contact is allowed, damage to either system can decrease attraction to vaginal secretion in sexually inexperienced male Syrian hamsters (Pfeiffer and Johnston, 1994; Powers et al, 1979) and mice (Pankevich et al, 2004) but not in sexually experienced Syrian hamsters (O’Connell and Meredith, 1984). Similarly, VNO removal in sexually inexperienced guinea pigs leads to rapid extinction of urine investigative behavior (Beauchamp et al, 1982).…”
Section: Chemosignals and Behavior: Malesmentioning
confidence: 99%
“…Urine and vaginal fluid have been widely recognized as significant sources of pheromones across numerous species, attributed to their capacity to modulate male sexual behaviour and reproductive functions [55][56][57]. While previous investigations have indicated that exposure of male rabbits to females elicits heightened sexual drive and improved semen characteristics [26], a comprehensive assessment of the specific female cues driving these alterations has not been undertaken.…”
Section: Doe Urine and Vaginal Fluid As Potential Biostimulatorsmentioning
confidence: 99%